2018
DOI: 10.1016/j.jas.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Can we identify the Mexican hairless dog in the archaeological record? Morphological and genetic insights from Tizayuca, Basin of Mexico

Abstract: The Mexican Hairless dog, or Xoloitzcuintle, is a breed characterised by a sparse hair coat and a severe oligodontia. This phenotype is a consequence of Canine Ectodermal Dysplasia (CED) caused by a mutation on the FoxI3 autosomal gene. First accounts of hairless dogs in Mexico are dated to the 16 th century CE, according to the historical record, but pre-Hispanic dog skeletons presenting missing and abnormally shaped teeth have been interpreted as earlier evidence of hairless dogs. However, several questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The fact that several dogs in the Gran Depósito possibly belonged to the hairless breed indicates they may have been specially selected for rituals. Currently, the earliest evidence for this breed is from Classic period deposits at Guadalupe (Rodríguez Galicia et al 2001), Tula (Valadez Azúa et al 1999), and Tizayuca (Manin et al 2018) in central Mexico. Other examples can be found throughout Mexico dating to the Postclassic period (AD 900–1500; Valadez Azúa 2020; Valadez Azúa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that several dogs in the Gran Depósito possibly belonged to the hairless breed indicates they may have been specially selected for rituals. Currently, the earliest evidence for this breed is from Classic period deposits at Guadalupe (Rodríguez Galicia et al 2001), Tula (Valadez Azúa et al 1999), and Tizayuca (Manin et al 2018) in central Mexico. Other examples can be found throughout Mexico dating to the Postclassic period (AD 900–1500; Valadez Azúa 2020; Valadez Azúa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The hairless breed likely originated in central Mexico based on zooarchaeological and genetic data (Blanco Padilla et al 2008; Manin et al 2018). Certain characteristics of the dog are depicted in Mexican precolumbian art, including its prominent wrinkles and large ears, although these images could also represent short-haired dogs (Valadez Azúa 1996, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hypotheses about the phylogenetic relationships between breeds have been generated from genomic data (Parker et al 2017), with some modern American breeds considered as basal (e.g., Alaskan Malamute, American Eskimo). There is substantial zooarchaeological and molecular evidence suggesting that pre-Columbian dogs are mostly extinct (including hairless dogs), and that these were replaced by the various European dog lineages (Leonard et al 2002;Castroviejo-Fisher et al 2011;Larson et al 2012;Thalmann et al 2013;Leathlobhair et al 2018;Manin et al 2018). Other authors have found evidence for a pre-Columbian origin and no modern European influence on Arctic ancient breeds such as Inuit, Eskimo, and Greenland dogs (Ameen et al 2019) , where the lateral view of B is mirrored.…”
Section: The Morphological Diversity Of Pre-columbian American Domest...mentioning
confidence: 99%
“…). Shared genetic markers among modern and archaeological specimens assigned to hairless dogs also suggest common ancestry(Manin et al 2018). Valdés 1944, on La Plata River Basin).…”
mentioning
confidence: 99%